Enhanced understanding of ectoparasite–host trophic linkages on coral reefs through stable isotope analysis. Issue 1 (April 2015) - Demopoulos, Amanda W.J.; Sikkel, Paul C.
Graphical Abstract: Highlights: Parasitic larval gnathiid isopods had δ 13 C and δ 15 N values similar to their host. Values were more similar to host heart and blood tissue than host muscle tissue. Adult gnathiids were enriched in 15 N and depleted in 13 C relative to larval stages. Anilocra isopods δ 13 C and δ 15 N values depended on their specific fish host. Gnathiid-fed cleaner shrimp were enriched in 15 N relative to their food source. Abstract: Parasitism, although the most common type of ecological interaction, is usually ignored in food web models and studies of trophic connectivity. Stable isotope analysis is widely used in assessing the flow of energy in ecological communities and thus is a potentially valuable tool in understanding the cryptic trophic relationships mediated by parasites. In an effort to assess the utility of stable isotope analysis in understanding the role of parasites in complex coral-reef trophic systems, we performed stable isotope analysis on three common Caribbean reef fish hosts and two kinds of ectoparasitic isopods: temporarily parasitic gnathiids ( Gnathia marleyi ) and permanently parasitic cymothoids ( Anilocra ) . To further track the transfer of fish-derived carbon (energy) from parasites to parasite consumers, gnathiids from host fish were also fed to captive Pederson shrimp ( Ancylomenes pedersoni ) for at least 1 month. Parasitic isopods had δ 13 C and δ 15 N values similar to their host, comparable with results from the small number of other host–parasite studies that have employed stable isotopes. Adult gnathiids were enriched in 15 N and depleted in 13 C relative to juvenile gnathiids, providing insights into the potential isotopic fractionation associated with blood-meal assimilation and subsequent metamorphosis. Gnathiid-fed Pedersen shrimp also had δ 13 C values consistent with their food source and enriched in 15 N as predicted due to trophic fractionation. These results further indicate that stable isotopes can be an effective tool in deciphering cryptic feeding relationships involving parasites and their consumers, and the role of parasites and cleaners in carbon transfer in coral-reef ecosystems specifically.